2006
DOI: 10.1093/aje/kwj321
|View full text |Cite
|
Sign up to set email alerts
|

Meta- and Pooled Analysis of GSTT1 and Lung Cancer: A HuGE-GSEC Review

Abstract: Lung cancer is the most common malignancy in the Western world, and the main risk factor is tobacco smoking. Polymorphisms in metabolic genes may modulate the risk associated with environmental factors. The glutathione S-transferase theta 1 gene (GSTT1) is a particularly attractive candidate for lung cancer susceptibility because of its involvement in the metabolism of polycyclic aromatic hydrocarbons found in tobacco smoke and of other chemicals, pesticides, and industrial solvents. The frequency of the GSTT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 84 publications
7
75
1
4
Order By: Relevance
“…The frequency of GSTM1-null genotypes in the control population (47.2%) in the present study was similar to what was published previously in metaanalyses and pooled analyses among Caucasians (21)(22)(23). However, the frequency of GSTT1-null geno type in our cohort (27.6%) was higher than the values repor ted among Caucasians (18.1%) (24).…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of GSTM1-null genotypes in the control population (47.2%) in the present study was similar to what was published previously in metaanalyses and pooled analyses among Caucasians (21)(22)(23). However, the frequency of GSTT1-null geno type in our cohort (27.6%) was higher than the values repor ted among Caucasians (18.1%) (24).…”
Section: Discussionsupporting
confidence: 89%
“…In the present meta-analysis, under the light of a nearly 3-fold increase in the number of eligible studies, a clear association between GSTT1 null genotype and increased breast cancer risk became evident and seemed indeed confined to non-Chinese populations. Race-specific effects of GSTT1 polymorphism status may not seem surprising at a meta-analytical level, as racespecific associations have been described in meta-analyses examining lung [73] and gastric [74] cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Careful analysis of the literature reveals a much more murky picture for the GSTT1 gene than for GSTM1. Although one group reported GSTT1 to be a risk factor for lung cancer, 11 the majority of studies have found no association between GSTT1 deletion and cancer as shown by a meta and pooled analysis, 12 and in general there are more negative findings for this variant than for the GSTM1 deletion. Even more interesting is the growing body of evidence that the GSTT1 deletion is actually protective in many studies.…”
mentioning
confidence: 99%
“…20 A significant negative interaction was observed between GSTT1 null and lung cancer in occupationally exposed subjects. 12 Speculations as to the mechanism of the protective effect of GSTT1 in human cancer have largely focused on the possibility that the products of GSTT1 conjugating reactions could produce in certain instances more carcinogenic metabolites, such as for the dihalomethanes and other chlorinated hydrocarbons, [21][22][23][24] which are known to be bioactivated by GSTT1. In addition, since the GST genes use certain chemopreventive compounds such as isothiocyanates as substrates, the deletion of GSTT1 could lead to the availability of higher levels of cancer preventing compounds.…”
mentioning
confidence: 99%